2013
DOI: 10.1002/mats.201300111
|View full text |Cite
|
Sign up to set email alerts
|

On the Discrimination of RAFT Models Using Miniemulsion Polymerization

Abstract: In RAFT miniemulsion polymerization, the slow fragmentation (SF) model reveals essentially the same polymerization rate as the corresponding bulk polymerization, while the intermediate termination (IT) model shows a drastic rate increase in a wide droplet size range, and thereby, two controversial models for the RAFT mechanism can be discriminated without difficulty. The theoretical background why the SF model does not show acceleration in miniemulsion polymerization is discussed. A simple equation to check th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
(105 reference statements)
1
17
0
Order By: Relevance
“…On the basis of the numerical calculations, using a wide range of parameters, it was concluded that the SF model does not show the polymerization rate increase by decreasing the particle size [23], as long as the given set of parameters cause the retardation behavior in bulk polymerization. Figure 7a,b show the simulation results for the conversion development during bulk and miniemulsion polymerization, by using the same set of parameters as in Figure 6.…”
Section: )mentioning
confidence: 99%
“…On the basis of the numerical calculations, using a wide range of parameters, it was concluded that the SF model does not show the polymerization rate increase by decreasing the particle size [23], as long as the given set of parameters cause the retardation behavior in bulk polymerization. Figure 7a,b show the simulation results for the conversion development during bulk and miniemulsion polymerization, by using the same set of parameters as in Figure 6.…”
Section: )mentioning
confidence: 99%
“…Theoretical investigation have clarified the rate difference quantitatively, and the equation predicting the threshold diameter below which significant acceleration occurs was derived . As reviewed in the theoretical section, the relationship between the miniemulsion polymerization rate and the droplet size has been elucidated theoretically . In the present article, the experiment was designed on the basis of the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Even for such a hybrid model, the determined model parameters could be classified into SF and IT, depending on the major reason for retardation. If the determined equilibrium constant k 1 / k 2 cannot cause retardation, the major reason for retardation would be the intermediate termination . Such cases could be considered belonging to the IT model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though RAFT polymerizations have been studied extensively, there is an ongoing debate regarding particular aspects of the kinetic mechanism. It has been observed that for certain RAFT agents, such as dithiobenzoates and some dithiocarbamates, there is rate retardation when the concentration of the RAFT agent is increased, as well as an induction period.…”
Section: Introductionmentioning
confidence: 99%